EVOLUTION OF ARCHITECTURAL FORMATION OF CENTRES OF SCIENTIFIC AND TECHNICAL CREATIVITY - Izirinskyi, Oleksandr (Theory and practice of design, 2025)
The centre of scientific and technical creativity is considered as a building or a complex of buildings where the development and transfer of knowledge in the field of science, technology and engineering takes place. Such centres combine educational, research and practical activities aimed at finding innovative solutions, creating new technologies or improving existing ones. Regardless of the era and formal definition, such functions have been performed by various historical structures: from the Library of Alexandria and Plato’s Academy to modern innovation hubs and technology parks. Purpose: to determine the main stages of formation of centres of scientific and technical creativity, to analyse the patterns and characteristics of their architectural and planning organisation. Methodology. The study of the architectural and planning organisation of centres of scientific and technical creativity of different historical periods was based on the method of systematic analysis, synthesis and generalisation of available bibliographic sources. The result of the study is the identification of the main stages of the formation of centres of scientific and technical creativity, the characteristic features of their architectural and planning organisation. The scientific novelty lies in the systematic analysis of the stages of evolution of centres of scientific and technical creativity through the prism of architectural and planning transformation. For the first time, the characteristic features of the centres of each historical period are summarised and the key features that led to changes in their spatial organisation are identified. The study allows us to identify patterns of development of architectural solutions in the context of social, technological and cultural changes. Practical relevance. The practical significance of the study lies in the fact that centres of scientific and technical creativity play an important role in the cultural, educational and scientific spheres of society. Thanks to this work, it is possible to trace changes in the architectural and planning organisation of science centres during different historical periods and understand the reasons for the formation of certain spatial solutions or the dominance of certain elements. This allows us not only to analyse the historical development of centres of scientific and technical creativity, but also to take into account the principles of their architectural and planning organisation in the modern design of centres, and to be the basis for practical solutions today.